Diversidade, cidadania e direitos: o design educacional de uma disciplina em EaD na Universidade Estadual de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This work is part of the Education, School, and Technologies research line of the Interdisciplinary Postgraduate Program in Education, Language, and Technologies. Its structure is based on discussing educational design for distance education (DL), amid the debate on human rights, by problematizing the technical-pedagogical and technological aspects that influence its construction. This debate is theoretically based on scholars, such as Candau (2012), Santos (2009) and Silva (2014), who discuss diversities; Moore and Kearley (2013), Aretio (2014), Filatro (2008), Kenski (2019), Moraes, Valentim and Souza (2019), Costa, Muriana and Melo (2021), Santaella (2003), Bordignon, Queiroz and Gomes (2011), A. Romiszowski and L. Romiszowski (2005), and Mattar (2014), which support the discussion of distance learning and educational design. The question that directs this work is: What are the constituent elements of educational design in distance learning at the State University of Goiás (UEG) and how is its construction process carried out by the multidisciplinary team of the Network Teaching and Learning Center (Cear/UEG), focusing on the common core subject, Diversity, Citizenship and Rights? As a main goal, it seeks to understand educational design in distance learning, based on the common core discipline, Diversity, Citizenship, and Rights. To this end, attention is drawn to the construction of educational design in the internal context of Cear from UEG, which is the locus of this research, focusing on the curricular component on screen, which is the case study on which we focus. In this work, we approach the phenomenological method. We start with a qualitative approach, exploratory research of the descriptive case study type, seeking to understand the phenomenon under construction of educational design in distance learning. Data collection uses document analysis instruments and semi-structured interviews with the multidisciplinary team from Cear/UEG. The results allow us to characterize the educational design in EaD at UEG as “transitional”, due to its technical focus, expressed in the methodological structuring previously defined in the analyzed discipline and the approach to student learning in a critical-reflective way, based on the socio-constructivist conception of the statements of the online activities and in the texts recommended for study in the discipline Diversity, Citizenship, and Rights. This transitional design is structured in the following stages: demand, mediation, assembly, and completion (DMMF). It is concluded that this educational design in distance learning at UEG is in motion and under construction. Still, it allows the elaboration of the Diversity, Citizenship, and Rights discipline with limitations in the development of digital folders due to the difficulty of a collective workflow in its stages by the multidisciplinary team.
Diversity, citizenship, and rights: the educational design of a distance learning discipline at the State University of Goiás
Keywords: Educação a distância - Universidade Estadual de Goiás; Design educacional - Disciplina em EaD - UEG; Distance learning - State University of Goias; Educational design - Distance learning discipline at UEG; CIENCIAS HUMANAS::EDUCACAO